Muslim networks and transnational communities in and across Europe - Allievi, Stefano; Nielsen, Jørgen S. (Muslim minorities ;, 2003)
The topic of this collection of articles is the increasingly transnational nature of Islam in Europe as well as the mechanisms by which the transnationalism is activated, especially the media. The papers integrate specific case studies with more general and thematic considerations.